2018
DOI: 10.1007/s11356-018-2968-0
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of innovation on CO2 emissions of OCED countries from 1990 to 2014

Abstract: Human activities are accelerating CO emissions all over the world most especially in high-income nations, spurring the rise in greenhouse gas emissions. For decades, technologies have been developed and patented in response to the environmental problems. There is an outcry for innovative ways to combat the environmental menace. This attests to the enormity of research being done, in recent years, to investigate how innovation can help mitigate CO emissions. This research aims at investigating into the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
136
3
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(169 citation statements)
references
References 71 publications
26
136
3
4
Order By: Relevance
“…A newly developed technology often exacerbates pollution if the original technology is not environmentally friendly. Moreover, there may also be an inverted U-shaped relationship between innovation and environmental impacts (Feng and Yuan, 2016;Mensah et al, 2018). Technological progress may start with a detrimental effect before it begins to exert a positive effect on the environment, similar to the mechanism of the environmental Kuznets curve (Grossman and Krueger, 1991).…”
Section: Innovation and Igdmentioning
confidence: 99%
“…A newly developed technology often exacerbates pollution if the original technology is not environmentally friendly. Moreover, there may also be an inverted U-shaped relationship between innovation and environmental impacts (Feng and Yuan, 2016;Mensah et al, 2018). Technological progress may start with a detrimental effect before it begins to exert a positive effect on the environment, similar to the mechanism of the environmental Kuznets curve (Grossman and Krueger, 1991).…”
Section: Innovation and Igdmentioning
confidence: 99%
“…Therefore, the expected sign of α 4 is positive. Also, R&D has been investigated as a potential factor of CO 2 emissions, and it lowers environmental pollution (Dauda, Long, Mensah, & Salman, ; Mensah, Long, Boamah, Bediako, & Dauda, ).…”
Section: Model and Datamentioning
confidence: 99%
“…Therefore, the expected sign of α 4 is positive. Also, R&D has been investigated as a potential factor of CO 2 emissions, and it lowers environmental pollution (Dauda, Long, Mensah, & Salman, 2019;Mensah, Long, Boamah, Bediako, & Dauda, 2018 (Ahmed, Wang, Mahmood, Hafeez, & Ali, 2019). The transport sector is measure as freight transport, refers to a total number of goods through domestic transport within a given network.…”
Section: Model and Datamentioning
confidence: 99%
“…emission as well as the interaction between ICT and GDP diminishes the intensity of pollution. The study by Mensah et al (2018) indicated that innovation (R&D) has a significant positive impact in reducing CO2 emissions in most OECD countries. Additionally, GDP intensifies CO2; in contrast, EKC is not applicable for most economies.…”
Section: Literature On Technology-co2 Emissionsmentioning
confidence: 99%
“…It indicates that technology is improving environmental quality by reducing CO2 emissions. The investigations conducted by Ang (2009); Sohag et al (2015); Ameer and Munir (2016); Salahuddin et al (2016); Yan et al (2017); Kahouli (2018); Khan et al (2018); Mensah et al (2018); Miao et al (2018); Xu and Lin (2018) revealed that different proxies of technology have a positive effect on environmental quality. Some of the scholars discovered the mixed or negative impact of technology on environmental quality (Choi and Han, 2018;Park et al, 2018).…”
Section: Introductionmentioning
confidence: 99%